Computed tomography findings in liver fibrosis and cirrhosis (Swiss Medical Weekly, 2014)
PRINCIPLES: Computed tomography (CT) is inferior to the fibroscan and laboratory testing in the noninvasive diagnosis of liver fibrosis. On the other hand, CT is a frequently used diagnostic tool in modern medicine. The auxiliary finding of clinically occult liver fibrosis in CT scans could result in an earlier diagnosis. The aim of this study was to analyse quantifiable direct signs of liver remodelling in CT scans to depict liver fibrosis in a precirrhotic stage. METHODS: Retrospective review of 148 abdominal CT scans (80 liver cirrhosis, 35 precirrhotic fibrosis and 33 control patients). Fibrosis and cirrhosis were histologically proven. The diameters of the three main hepatic veins were measured 1–2 cm before their aperture into the inferior caval vein. The width of the caudate and the right hepatic lobe were divided, and measured horizontally at the level of the first bifurcation of the right portal vein in axial planes (caudate-right-lobe ratio). A combination of both (sum of liver vein diameters divided by the caudate-right lobe ratio) was defined as the ld/crl ratio. These metrics were analysed for the detection of liver fibrosis and cirrhosis. RESULTS: An ld/crl-r